Oxidative Stress Markers Differ in Two Placental Dysfunction Pathologies: Pregnancy-Induced Hypertension and Intrauterine Growth Restriction. (30th June 2020) - Zygula, Aleksandra; Kosinski, Przemyslaw; Wroczynski, Piotr; Makarewicz-Wujec, Magdalena; Pietrzak, Bronislawa; Wielgos, Mirosław; Giebultowicz, Joanna
Abstract : Aim . Pregnancy-induced hypertension (PIH) and intrauterine growth restriction (IUGR) are both multisystemic disorders of pregnancy that cause perinatal morbidity and mortality. Recently, researchers focused on the role of oxidative stress (OS) as a pathophysiological mechanism in the development of these pathologies. The aim of this study was to compare OS in placental-related pathologies (PIH and IUGR) and uncomplicated pregnancies. We also investigated which salivary OS markers reflect systemic oxidative status and which only reflect the state of the oral cavity. Material and Methods . A total of 104 pregnant women (n = 104 ; 27 with PIH, 30 with IUGR, and 47 controls) were evaluated. Malondialdehyde (MDA), total antioxidant capacity (ORAC), aldehyde dehydrogenase (ALDH), and activity of glutathione peroxidase (GPx) and glutathione transferase (GST) in plasma/whole blood and/or saliva were analysed. Dietary nutrient intake was calculated using a Semiquantitative Food Frequency Questionnaire (SFFQ). Oral health was assessed to eliminate patients with bleeding, severe periodontitis, and other dental pathologies. Results . In the IUGR group, increased concentration of ORAC was observed both in saliva and plasma. Also, lower plasma levels of MDA in IUGR compared to the control group was detected. No sign of oxidative stress was confirmed in the PIH group. The examined groups did not differ regarding diet and markers of inflammation. ORAC in saliva was correlated with its level in plasma. No such correlations for MDA were observed. In the IUGR group, there were no differences in OS markers in plasma, but there was a lower ALDH level in the blood compared to the control group. It confirms OS occurrence in IUGR. In IUGR, a higher activity of salivary ALDH was probably due to worse oral health. Conclusion . Oxidative stress differs between IUGR and PIH groups: the presence of oxidative stress was confirmed only in the IUGR group. Salivary ORAC can be used to estimate ORAC in plasma. The activity of salivary ALDH reflects the state of the oral cavity.